2019
DOI: 10.1177/2399369319865271
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced kidney injury

Abstract: Renal dysfunction because of radiation exposure was recognized decades ago. The incidence declined when more effective chemotherapeutic agents became available. However, there appears to be a resurgence with the advent of total body irradiation used prior to hematopoietic stem cell transplantation. Several chemotherapeutic drugs used prior to total body irradiation have some ionizing radiation potentiating effects. Chronic kidney disease that occurs after hematopoietic stem cell transplantation is known to occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Single fraction radiation doses as low as 4 Gy may lead to renal injury, and a prior study found that radiation nephropathy was found in 20% of irradiated subjects. 4 The absence of any signs or symptoms of kidney injury at the time of re-treatment should not be considered as absence of latent or residual injury. Doses of radiation may sometimes be too low to produce overt damage but do significantly reduce the tolerance to re-treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single fraction radiation doses as low as 4 Gy may lead to renal injury, and a prior study found that radiation nephropathy was found in 20% of irradiated subjects. 4 The absence of any signs or symptoms of kidney injury at the time of re-treatment should not be considered as absence of latent or residual injury. Doses of radiation may sometimes be too low to produce overt damage but do significantly reduce the tolerance to re-treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying CKD due to hypertension or diabetes, liver diseases, heart disease, and smoking can also reduce the tolerance to RT. 4 However, the impact of these variables is not well recognized. There is great uncertainty among the dose-volume recommendations since only a few studies are based on long term follow ups.…”
Section: Discussionmentioning
confidence: 99%
“…Critically, some types of soluble Klotho may exist in the blood, urine and other body fluids, where it performs a multitude of functions in renal inflammatory response. However these pleiotropic roles are poorly understood (8,(41)(42)(43). Moreover, the differences between BALB/c and C57BL/6 mice with regards to changes in TNF-α and ADAM9/10/17 expression caused by irradiation may be assessed in future research.…”
Section: Discussionmentioning
confidence: 99%
“…[ 161 ] Clinical symptoms include edema, fatigue, malignant hypertension, anemia, azotemia, and breath shortness. [ 162,163 ] Regarding the injury mechanisms and as a paradigm, Balabanli et al. studied the role of free radicals in the radiation nephropathy mechanism.…”
Section: Nanomaterials Design For Prevention and Treatment Of Various mentioning
confidence: 99%
“…reviewed the pathophysiological changes in irradiated kidneys, including glomerular changes, tubulo‐interstitial injury, vascular injury, and functional changes. [ 163 ] Adhikari et al. had already achieved nanomaterial‐mediated kidney radiation disease treatment at the cellular level, in 2015.…”
Section: Nanomaterials Design For Prevention and Treatment Of Various mentioning
confidence: 99%